Enhancement of Bio-plastic using Eggshells and Chitosan on Potato Starch Based - Kasmuri, Norhafezah; Muhammad Abu Zait, Safwan (International Journal of Engineering and Technology, 2018)
The extensive production of polymer plastics and their use in different commercial applications had burdened the municipal in cost and operation of the waste management system. This unwanted waste had also posed a significant threat to the environmental surroundings which destroyed biota. Hence, alternatives called bio-plastic evolved as the development of renewable resource by utilizing agricultural, eggshells and exo-skeleton seafood (chitosan) wastes instead of petroleum sources. The aim of this research is to use the eggshells and chitosan as fillers in potato starch to overcome the inherent drawbacks of bio-plastic. The experimental study was done on tensile strength, water absorption and biodegradability for potato starch-based bio-plastic with eggshells or chitosan. The results showed that by adding the eggshells into the potato starch-based bio-plastic had increased the tensile strength by 4.94% compared with chitosan only 1.28%. The reduction of water absorption by 10.95% was determined using eggshells as fillers. Meanwhile, the used of chitosan resulted in 27.59% reduction in water absorption. In eggshells, the weight loss in biodegradability test was 21.06% compared to chitosan of 7.9% within 20 days. It can be concluded that eggshells as fillers performed much better that chitosan in potato starch-based bio-plastic. It also can be deduced that adding fillers in starch-based bio-plastics can improve the bio-plastic performance.
Keywords: biodegradability; bio-plastic; chitosan; eggshells; potato starch; shrimp shells; tensile strength; water absorption.